Insights into the Effect of Micropore Structure and Mineralogy on Adsorbed Tight Oil in the Huaqing Area, Ordos Basin, China - Qianshan Zhou; Dongwei Zhang; Mingli Xi; Yilin Zhao; Chao Li; Guojun Chen; Chengfu Lyu; Xiaofeng Ma (Geofluids)
There is great potential for tight oil as an alternative to conventional fossil fuels throughout the world. Adsorption, mineralogy, and pore structure of tight sandstone are very important factors for the efficient development of adsorbed tight oil from tight sandstone oil reservoirs. In this study, the occurrence morphology of tight oil adsorbed to varying pore structures was examined, as well as the relationship between adsorption content and occurrence morphology. X-ray energy dispersive spectra, environmental scanning electron microscope observations, and thin fluorescence sections were used to describe the occurrence morphology of adsorbed tight oil in tight sandstone reservoirs. It was found that adsorbed tight oil can be classified into five types: emulsion, cluster, throat, thin-film, and isolation, with average contents of 34.9%, 14.5%, 3.1%, 42.7%, and 4.7%, respectively. In addition, a Soxhlet extraction was developed with four pore structures to describe the geological effects of adsorbed tight oil in reservoirs. The adsorption content of tight oil ranges from 4.015 mg/g to 16.987 mg/g, with an average of 10.115 mg/g. The order of adsorption content for different occurrence morphologies is as follows: emulsion form > throat form > cluster form > isolation form > thin-film form. It is the size and connectivity of the porous throat that determines the desorption efficiency of tight oil. An important outcome of this study can be the introduction of rational development plans and the improvement of oil recovery efficiency for tight oil reservoirs.